Methodologies and Techniques for Advanced Maintenance - Fedele, Lorenzo; SpringerLink (Online service) (London : Springer London, 2011)
The management of technical plants for productivity and safety is generally a complex activity, particularly when many plants in one territory are affected, quality guarantees and cost results are required, and the technology involved is heterogeneous and innovative. To enable readers to manage technical plants efficiently, despite the above complications, Methodologies and Techniques for Advanced Maintenance presents theories, methodologies and practical tools for the realization of an intelligent maintenance management system for distant monitoring. It also covers the development and running of a remote control center. The so-called granted availability management system (GrAMS) was conceived to enable organizations involved in technical-industrial plant management to move towards "well known availability" and "zero failures" management. In particular, Methodologies and Techniques for Advanced Maintenance deals with the diagnostic aspects and safety levels of technical plants (such as elevators, thermo-technical plants, etc.). The author also discusses the usage of ad hoc designed software analysis tools based on neural networks and reliability indicators. Methodologies and Techniques for Advanced Maintenance is a useful text for practitioners and researchers in maintenance and facilities. Its application spans industrial, plant, technological, infrastructure and civil fields.
1. Introduction -- 2. Planning and Managing Maintenance -- 3. The Life Cycle of Products and Systems and Logistical Engineering -- 4. Maintenance Policies and Strategies -- 5. From Basic Maintenance to Advanced Maintenance -- 6. Testability and Prognostics -- 7. Intelligent Telematic Maintenance Systems for the Management of Technical Plants -- 8. Model for the Overall Evaluation of Management and Maintenance Contracts -- 9. The System of Unified Diagnostics and Standard Maintenance of Bridges and Infrastructures.
Keywords: Engineering; Building construction; Telecommunication; Engineering; Facility Management; Building Repair and Maintenance; Communications Engineering, Networks